Modern architecture pop-up book - Radevsky, Anton; Sokol, David M. (New York : Universe, 2008)
Showcases three-dimensional replications of some of the most innovative modern and contemporary architecture from around the world.
Cover title.
Keywords: Architecture, Modern -- Juvenile literature; Pop-up books -- Specimens